Method for preparing lanthanum gallate-based oxygen ion conductor electrolyte
By optimizing the casting process and solvent selection, the cracking and cost problems in the preparation of LaGaO3-based oxide electrolytes were solved, realizing the preparation of efficient and low-cost lanthanum gallate-based oxygen ion conductor electrolytes, and improving the mechanical strength and performance of the electrolyte sheet.
Patent Information
- Application Number
- CN202411874811.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing technologies for preparing LaGaO3-based oxide electrolytes suffer from complex preparation processes, high costs, and the tendency to crack during the green body ceramicization stage, which limits their large-scale production and widespread application.
A casting process using mixed organic solvents and dispersants was employed. Lanthanum gallate-based powder was prepared by ball milling a mixture of La2O3, SrCO3, Ga2O3, and MgO raw material powders with anhydrous ethanol and butanone. The powder was then mixed with a dispersant and binder to form a slurry. After casting, drying, debinding, and high-temperature sintering, the preparation process was optimized to obtain a dense electrolyte sheet.
It improves the surface smoothness and uniformity of lanthanum gallate-based oxygen ion conductor electrolytes, reduces bubbles, wrinkles and cracks in the blank, simplifies the preparation process, reduces particle size and cost, and improves the mechanical strength and performance of electrolyte sheets.
Smart Images

Figure CN119330712A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte. Background Art
[0002] Solid Oxide Fuel Cell (SOFCs) is a clean and efficient energy conversion technology. It has attracted widespread attention for its high energy density, wide application fields, and high adaptability to a variety of fuels. Solid oxide fuel cells can directly convert chemical energy into electrical energy at high temperatures, thus providing an efficient way to achieve sustainable energy conversion. The electrolyte material is the core component of SOFC. Its function is to conduct oxygen ions between the cathode and the anode and separate the fuel gas from the oxidant. Therefore, the requirements for its performance are also quite stringent, requiring it to have high ionic conductivity and ion migration number, good thermal stability and chemical stability. LaGaO3-based oxides have excellent ionic conductivity and good chemical stability, can efficiently transport oxygen ions at lower temperatures, and have broad application prospects in the field of solid oxide fuel cells.
[0003] Although LaGaO3-based electrolyte materials have shown great application potential in the fields of energy, information, aerospace, etc. due to their excellent performance, they face a series of challenges in the actual preparation process. These challenges mainly come from their complex preparation process and expensive cost, especially the low efficiency in large-scale production. In addition, there is a large stress in the green body obtained by the traditional dry pressing method, which makes the green body easy to crack during the porcelain stage, and it is difficult to prepare electrolyte sheets with sufficient mechanical strength. These restrictive factors have seriously hindered the development of LaGaO3-based oxides in practical applications.
[0004] Although the prior art proposes an organic tape casting process, this process is mainly suitable for the preparation of specific powders such as gadolinium-doped cerium oxide and yttrium-stabilized zirconia. This process has problems such as uneven distribution of strontium oxide and magnesium oxide when preparing lanthanum strontium gallium magnesium powder, as well as warping and cracking during sintering. These problems limit the effectiveness of this technology in a wider range of application scenarios. For this reason, a method for preparing lanthanum gallate-based oxygen ion conductor electrolyte is proposed. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte, which solves the problems in the prior art.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte comprises the following steps: The raw material powders of La2O3, SrCO3, Ga2O3 and MgO are mixed with an organic solvent and then ground, and then calcined and ground to obtain lanthanum gallate-based powder; The lanthanum gallate-based powder, the dispersant and the solvent are mixed and ground, and then a plasticizer and a binder are added and further ground to obtain a slurry; The slurry is subjected to vacuum degassing and filtration; thereafter, it is subjected to tape casting to obtain a cast film; The cast film is peeled off from the film tape after drying, cut into green blanks by a puncher, and after debinding and sintering, a lanthanum gallate-based oxygen ion conductor electrolyte is obtained.
[0007] Furthermore, the molar ratio of La2O3, SrCO3, Ga2O3, and MgO raw material powders is (0.35-0.5): (0-0.3): (0.35-0.5): (0-0.3).
[0008] Furthermore, the organic solvent is anhydrous ethanol.
[0009] Furthermore, the calcination temperature is 1100°C.
[0010] Furthermore, when preparing the slurry, the mass parts of lanthanum gallate-based powder are 40-60 parts, the mass parts of solvent are 30-40 parts, the mass parts of dispersant are 5-10 parts, the mass parts of adhesive are 1-5 parts, and the mass parts of plasticizer are 1-10 parts.
[0011] Furthermore, the solvent is a mixture of anhydrous ethanol and butanone in a mass ratio of 3:2.
[0012] Furthermore, the dispersant is triethanolamine.
[0013] Furthermore, the plasticizer is a mixture of polyethylene glycol and dibutyl phthalate.
[0014] Furthermore, the debinding temperature is 1000° C. for 3-5 hours, and the sintering temperature is 1450° C. for 7-10 hours.
[0015] Furthermore, the travel speed of the tape casting process is 0.3-0.7 cm·s -1 , the total scraper height is 1500µm.
[0016] Beneficial effects of the present invention: 1. The present invention obtains slurry by mixing raw material powder with organic solvent and ball milling, and then obtains green blank by casting and drying, and finally obtains dense La by debinding and high temperature sintering. 1-x Sr x Ga 1-y Mg yO3 (x=0-0.3, y=0-0.3) electrolyte substrate. Compared with the existing process, the present invention optimizes the solid phase reaction method for synthesizing LSGM powder, screens solvents for lanthanum gallate-based electrolyte slurry, determines the composition and formula of the casting slurry, and the casting parameters of the blank. The blank obtained by casting has better quality, optimizes the surface flatness of the lanthanum gallate-based electrolyte sheet, and reduces the occurrence of bubbles, wrinkles, cracks, and even the difficulty of the blank falling off the film tape.
[0017] 2. The present invention does not require the use of pure phase La 1-x Sr x Ga 1-y Mg y O3 powder is used as raw material, avoiding the two-step sintering process in the solid phase reaction method and reducing the La 1-x Sr x Ga 1-y Mg y Preparation process of O3 electrolyte sheet. The synthetic LSGM powder raw materials were ball-milled in ethanol for 12 hours to reduce the particle size of each raw material from 5-10µm to 1-3µm; the agglomeration between particles was reduced, thereby reducing the size of the reactant particles, improving the mixing uniformity of the reactant particles, and increasing the contact interface of the reactant particles.
[0018] 3. The present invention adopts a mixture of anhydrous ethanol and butanone. Compared with a single solvent, the mixed solvent is widely used in the tape casting process due to its better comprehensive properties, such as better surface tension and dielectric constant, and lower boiling point; and the viscosity of anhydrous ethanol, butanone and LSGM powder after mixing is moderate, and the sedimentation rate is slow, which is better than other solvents.
[0019] 4. In the solvent system of anhydrous ethanol and butanone, other components are constant. Comparing the sedimentation effects of different dispersants, triethanolamine has the smallest viscosity, faster sedimentation, the best dispersion effect, and stable slurry, making it suitable as a dispersant for this system.
[0020] 5. The binder of the present invention is polyvinyl butyral, and the plasticizer is a mixture of dibutyl phthalate and polyethylene glycol; wherein dibutyl phthalate can act on the binder and dissolve polyvinyl butyral as a solvent; and polyethylene glycol forms an organic bridge between powder particles, which can increase the viscosity of the slurry. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0022] Figure 1 is a flow chart of the preparation method of the present invention; Figure 2 The La prepared by the present invention 0.9 Sr 0.1 Ga 0.8 Mg 0.2 XRD pattern of O3 electrolyte; Figure 3 It is a graph showing the results of the sedimentation test and viscosity test of different solvents of the present invention; Figure 4 is a graph showing the results of sedimentation tests of different dispersants of the present invention; Figure 5 It is an AC impedance spectrum of the electrolyte sheet prepared by the present invention at 700°C-850°C; Figure 6 The La prepared by the present invention 0.9 Sr 0.1 Ga 0.8 Mg 0.2 Morphology of O3 electrolyte. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] A method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte comprises the following steps: S1, according to La 1-x Sr x Ga 1-y Mg y Prepare the raw material powders of La2O3, SrCO3, Ga2O3 and MgO in the stoichiometric ratio of O3 (x=0-0.3, y=0-0.3); mix the prepared raw material powders with the organic solvent and grind them thoroughly in a planetary ball mill for 12 hours at a speed of 100-200 r·min -1 After mixing and grinding, the mixture was calcined at 1100°C for 5h, and then ground to obtain lanthanum gallate-based powder (LSGM).
[0025] S2, add lanthanum gallate-based powder, dispersant and solvent into a planetary ball mill and grind them for 24 hours at a speed of 100-300 r·min -1 , break up the particle agglomeration and wet the powder to achieve the dispersion effect; then add the plasticizer and binder, and continue grinding for 24-48 hours to obtain the slurry, and the grinding speed is 200-400r·min -1; S3, vacuum degassing and filtering the obtained slurry to remove air and other insoluble impurities mixed in the slurry; then the slurry is subjected to tape casting to obtain a cast film at a speed of 0.3-0.7 cm·S -1 , the total height of the scraper is 1500µm; S4, the cast film after casting is dried and peeled off from the film tape, cut into blanks by a puncher, and after debinding and high-temperature sintering, a lanthanum gallate-based oxygen ion conductor electrolyte substrate is obtained. The molecular formula of the lanthanum gallate-based oxygen ion conductor electrolyte is La 1- x Sr x Ga 1-y Mg y O3(x=0-0.3,y=0-0.3).
[0026] In S1, the molar ratio of La2O3, SrCO3, Ga2O3, and MgO raw material powders is (0.35-0.5): (0-0.3): (0.35-0.5): (0-0.3); In S1, the organic solvent is anhydrous ethanol; In S2, the mass parts of lanthanum gallate-based powder are 40-60 parts, the mass parts of solvent are 30-40 parts, the mass parts of dispersant are 5-10 parts, the mass parts of binder are 1-5 parts, and the mass parts of plasticizer are 1-10 parts; In S2, the solvent is a mixture of anhydrous ethanol and butanone in a mass ratio of 3:2, the dispersant is triethanolamine, and the plasticizer is a mixture of polyethylene glycol and dibutyl phthalate.
[0027] In S4, the drying time is 12 h and the drying temperature is 80°C.
[0028] In S4, the debinding temperature is 1000° C. for 3-5 hours; the high-temperature sintering temperature is 1450° C. for 7-10 hours.
[0029] The technical solution of the present invention is described below by the following embodiments; Example 1 Weigh 18 mol La2O3, 4 mol SrCO3, 16 mol Ga2O3, 8 mol MgO and 30 g anhydrous ethanol, mix well and grind thoroughly in a planetary ball mill for 12 h at a speed of 200 r / min. -1 After mixing and grinding, the mixture was calcined at 1100°C for 5 hours, and then taken out and ground to obtain lanthanum gallate-based powder. 21g of lanthanum gallate-based powder (LSGM) and 12g of solvent were weighed, and viscosity and deposition tests were performed to select the best solvent.
[0030] The samples after mixing different solvents and lanthanum gallate-based powders are shown in Table 1 below: Table 1 Mixing formula of different solvents and lanthanum gallate-based powders The test steps for viscosity and sedimentation of the five samples in Table 1 are as follows: the sample container is placed in a constant temperature water bath at 40°C, the capillary viscometer is filled with the sample to be tested, the stopcock is opened, the sample begins to flow to the liquid receiver, and when the sample liquid level reaches the scale line, the flow time in the tube is calculated; after the sample is left to stand for 1 hour, the sedimentation heights of samples with different solvents are compared.
[0031] The test results are as follows Figure 3 As shown in the figure, it can be seen that anhydrous ethanol / butanone settles faster as a solvent, and has moderate viscosity and good fluidity, indicating that anhydrous ethanol / butanone is suitable as a solvent for this system.
[0032] Example 2 Weigh 18 mol La2O3, 4 mol SrCO3, 16 mol Ga2O3, 8 mol MgO and 30 g anhydrous ethanol, mix well and grind them in a planetary ball mill for 12 h at a speed of 200 r / min. -1 ; After mixing and grinding, calcination at 1100°C for 5h, taking out and grinding to obtain lanthanum gallate-based powder. Weigh 21g of lanthanum gallate-based powder, 12g of ethanol / butanone (3:2), and 2.4g of dispersant; obtain samples containing different dispersants; and compare the deposition heights of different dispersants after the samples are left to stand for 1h.
[0033] Among them, the sample formulas containing different dispersants are shown in Table 2 below: Table 2 Sample formulas of different dispersants The deposition height test results of the four samples in Table 2 are as follows Figure 4 As shown in the figure, it can be seen that triethanolamine settles faster as a dispersant and has the best dispersion effect, which shows that triethanolamine is suitable as a dispersant for this system.
[0034] Example 3 In this embodiment, based on the solvent and dispersant formula selected from the results of Embodiment 1 and Embodiment 2, a method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte is proposed, comprising the following steps: S1, weigh 18molLa2O3, 4molSrCO3, 16molGa2O3, 8molMgO and 30g anhydrous ethanol, mix well and grind in a planetary ball mill for 12h at a speed of 200r·min -1 After mixing and grinding, the mixture was calcined at 1100°C for 5 hours, and then ground to obtain lanthanum gallate-based powder.
[0035] S2: Weigh 21 g of lanthanum gallate powder, 12 g of ethanol / butanone (3:2), and 2.4 g of triethanolamine, add them into a planetary ball mill and grind them thoroughly for 24 h at a speed of 300 r / min. -1 Then, 2.1 g of plasticizer (mixed with polyethylene glycol and dibutyl phthalate) and 1.3 g of binder (polyvinyl butyral) were added, and the mixture was ground for 48 h to obtain a slurry at a grinding speed of 400 r / min. -1 .
[0036] S3, the slurry is vacuum degassed and filtered, and then the slurry is tape-cast at a speed of 0.7 cm·s -1 , the total scraper height is 1500µm.
[0037] S4, the cast film after casting is dried and peeled off from the film tape, cut into blanks by a puncher, and after debinding and high-temperature sintering, a lanthanum gallate-based oxygen ion conductor electrolyte substrate is obtained. The molecular formula of the lanthanum gallate-based oxygen ion conductor electrolyte is La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O3, its XRD pattern is as follows Figure 2 shown.
[0038] Among them, the debinding temperature is 1000℃ and the time is 5h; the high-temperature sintering temperature is 1450℃ and the time is 10h.
[0039] The AC impedance spectrum of the lanthanum gallate-based oxygen ion conductor electrolyte prepared in Example 3 at 700°C-850°C is as follows: Figure 5 As shown, from Figure 5 It can be seen that the ohmic resistance of the prepared electrolyte sheet at 850°C is 0.11Ω·cm 2 It can be seen that the ohmic resistance of the electrolyte sheet prepared in this embodiment is not much different from the performance of the electrolyte sheet prepared by the existing process, which shows the feasibility of the invented process.
[0040] In addition, the morphology of the lanthanum gallate-based oxygen ion conductor electrolyte prepared in Example 3 is as follows: Figure 6 As shown, Figure 6 It can be seen that the electrolyte surface and cross section are dense and have almost no holes, which indicates that the present invention can prepare a sufficiently dense electrolyte sheet.
[0041] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0042] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte, characterized in that: The following steps are involved: The raw material powders of La2O3, SrCO3, Ga2O3 and MgO are mixed with an organic solvent and then ground, and then calcined and ground to obtain lanthanum gallate-based powder; The lanthanum gallate-based powder, the dispersant and the solvent are mixed and ground, and then a plasticizer and a binder are added and further ground to obtain a slurry; The slurry is subjected to vacuum degassing and filtration; thereafter, it is subjected to tape casting to obtain a cast film; The cast film is peeled off from the film tape after drying, cut into green blanks by a puncher, and after debinding and sintering, a lanthanum gallate-based oxygen ion conductor electrolyte is obtained.
2. The method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1, characterized in that: The molar ratio of La2O3, SrCO3, Ga2O3, and MgO raw material powders is (0.35-0.5): (0-0.3): (0.35-0.5): (0-0.3).
3. The method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1, characterized in that: The organic solvent is anhydrous ethanol.
4. The method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1, characterized in that: The calcination temperature is 1100°C.
5. The method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1, characterized in that: When preparing the slurry, the mass parts of lanthanum gallate-based powder are 40-60 parts, the mass parts of solvent are 30-40 parts, the mass parts of dispersant are 5-10 parts, the mass parts of binder are 1-5 parts, and the mass parts of plasticizer are 1-10 parts.
6. A method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1 or 5, characterized in that: When preparing the slurry, the solvent is a mixture of anhydrous ethanol and butanone in a mass ratio of 3:
2.
7. A method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1 or 5, characterized in that: The dispersant is triethanolamine.
8. A method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1 or 5, characterized in that: The plasticizer is prepared by mixing polyethylene glycol and dibutyl phthalate.
9. The method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1, characterized in that: The debinding temperature is 1000° C. for 3-5 hours; the sintering temperature is 1450° C. for 7-10 hours.
10. The method for preparing a lanthanum gallate-based oxygen ion conductor electrolyte according to claim 1, characterized in that: The travel speed of the tape casting process is 0.3-0.7 cm·s -1 , the total scraper height is 1500µm.
Citation Information
Patent Citations
Method for preparing flat-plate type metal-support solid oxide fuel cell
CN102881930A
Method for simply and conveniently preparing LaGaO3-based electrolyte sheet
CN117229057A
Support type lanthanum gallate-based oxygen ion conductor electrolyte membrane and preparation method thereof
CN118156564A
Preparation method of water-based tape casting slurry, method for preparing ceramic substrate and ceramic substrate
CN118184344A